Oral Health and Systemic Disease: A Systematic Review of the Impact of Dental Care on Overall Health - Merza, Randa fouad; Alqahtani, Nadeen Saeed; Al-sulami, Sarah Bakheet Bakheet; sindi, Johara abid; kabli, Razan sadiq yousif; alluqmani , Shahad hamoud; Aljohani, Rasha Bakheet; Saleh, Muna Abdullah; Hawsawi, Samiah Mohammed Abdullah; Aljahdali , Bayan Abdullah Sadeq; Alata, Abeer Jameel Abdulaziz (Journal of Ecohumanism, 2024)
Oral health is increasingly recognized as a critical component of overall health, with research highlighting its potential impact on various systemic diseases. This systematic review examines the current evidence on the association between oral health, particularly dental care, and systemic conditions such as cardiovascular disease, diabetes, respiratory illnesses, and adverse pregnancy outcomes. A comprehensive literature search was conducted across multiple databases, focusing on studies published from 2016 onward. Studies indicate that periodontal disease and other oral health issues may contribute to systemic inflammation, a common factor in many chronic conditions. Specifically, findings suggest that managing oral health can have beneficial effects on cardiovascular health, glycemic control in diabetic patients, and respiratory function, as well as reduce risks for adverse pregnancy outcomes. However, while associations are evident, causality remains difficult to establish, and further longitudinal research is needed to clarify these relationships. This review underscores the importance of incorporating dental care into holistic health approaches, advocating for greater collaboration between dental and medical professionals. Public health initiatives promoting regular dental check-ups and preventive care may play a crucial role in improving overall health outcomes.